Alterações ultraestruturais da cromatina espermática e sua associação com a proteômica da cabeça do espermatozoide em bovinos (bos taurus) - Rocha, Lays Oliveira (2019)
Changes in sperm chromatin in bulls may interfere with the fertilization process and embryonic development. Several methods are currently used to evaluate sperm chromatin, which use light microscopy to cytometry flow. Transmission electronic microscopy (TEM) has been used most frequently. These methodologies may identify from DNA fragmentation, to the intensity of chromatin compaction, which, if not adequate, makes the DNA susceptible to several damages or may be the morphological expression of epigenetic alterations. The objective of this work was to correlate chromatin alterations identified by TEM with the protein constitution of the bull spermatozoa head. Semen samples from four Girolando bulls were used, which were evaluated by TEM. Part of the samples were also used in in vitro embryo production routines (IVEP) and for analysis in advanced mass spectrometry, obtaining the semiquantitative protein composition of the spermatozoa head. In the TEM evaluation, chromatin compaction changes were divided into two types: mild (presence of up to 6 small clear spots or lighter region occupying up to a quarter of the head) and severe (presence of more than six light spots or occupying clearer region more than a quarter of the nuclear area). To identify possible correlations between the chromatin changes with the fertilization process and the initial embryonic development, the Pearson correlation test was performed between the percentage amount of each type of alteration with the cleavage and blastocyst rates obtained in the IVEPs, respectively. Considering that, dispate to the severe alterations, mild chromatin alterations did not present a significant correlation with the results of the IVEPs, only the existence of a correlation between the protein content of the head and the severe chromatin alterations was evaluated. To identify these correlations, Pearson's correlation test was used between the amount of each protein and the percentage of severe chromatin changes. To identify these correlations, Pearson's correlation test was used between the amount of each protein and the percentage of severe chromatin changes. Among the 766 proteins identified by mass spectrometry, the "60S ribosomal protein L12", "60 kDa heat shock protein", "Acetyl-CoA acetyltransferase", "Cytochrome b-c1 complex subunit 6", "ATP 342 synthase subunit delta "," Limbin "," 40S ribosomal protein S7 "," DNA replication ATP-dependent helicase / nuclease DNA2 "and" Activated CDC42 kinase1 "showed a significant positive correlation with severe chromatin alterations. These proteins may be directly or indirectly participating in the compaction process or only be present in large quantities when optimal conditions for compaction are present. On the other hand, the proteins Serine / threonine-protein phosphatase 2A, 60S ribosomal protein L9, Plasma serine protease inhibitor, Coiled-coil domain-containing protein 63, Signal peptidase complex subunit 3, Serine racemase, , "3-hydroxyisobutyrate dehydrogenase", "T-complex protein 1 subunit gamma", "Inositol monophosphatase 1", "Monofunctional C1-tetrahydrofolate synthase" showed significant negative correlation with severe chromatin alterations. The presence of these proteins may be directly or indirectly damaging the chromatographic compaction process or even they are only present in large quantities when the conditions for chromatographic compaction are not good. In any case, they have the potential to be used as molecular markers of subfertility and fertility, respectively.